Effects of Using Instructional Materials on the Academic Performance of Secondary School Students’ in Economics in Jos-North Local Government Area of Plateau State - Azi, A.S.; Dajan, H.J. (Kashere Journal of Education, 2022)
This study was carried out to investigate the effects of using instructional materials on the academic performance of senior secondary school students’ in economics in Jos-North Local Government Area of Plateau State. Two research questions were used for the study. The design of the study was experimental: the area of the study was two secondary schools (one public and one private secondary school) out of 22 public schools and 97 private schools in Jos-North Local government area of Plateau state. The sample of the study was 87, comprising of 44 and 43 SS 2 Economics students respectively. The research questions were analyzed using descriptive statistics such as mean, standard deviation and standard error mean. The instrument used in the study was the Economics Students’ Achievement Test (ESAT). The instrument was a 20-item multiple choice test covering the following topics: the theory of demand and supply and population, which were covered during instruction. The instrument was trial tested on 20 students selected from a different school outside the study area using the Kuder-Richardson formula and the reliability of 0.84 was obtained. Hence, the reliability co-efficient was found to be reliable. The students were grouped into experimental and control groups by way of randomization. The findings showed that the experimental group scored higher than the control group which indicates that the use of instructional materials was more effective in teaching economics in secondary schools. Based on the findings of the study, it was recommended among others that teachers should be trained and re-trained through workshops, seminars and conferences in order to acquire necessary skills for the improvisation and utilization of instructional materials for teaching economics.